Wildlife Forensics Using SNP Markers (Zoological Archives: An International Journal, 2026)
Wildlife forensics -- the application of genetic techniques to identify species, individuals, and geographic origins ofbiological material seized in wildlife crime investigations -- is a critical tool for law enforcement under CITES and nationalwildlife protection legislation, yet the genetic methods used in operational forensic casework remain underpowered formany taxa and provenance questions. This study developed and validated a 284-SNP panel for wildlife forensicapplications across 42 priority species (mammals: 18; birds: 12; reptiles: 8; fish: 4) by analysing 2,840 individuals fromgeoreferenced reference populations in 28 countries (2019-2024), using DArTseq reduced-representation sequencing forpanel discovery and Fluidigm EP1 microfluidic array genotyping for operational casework validation. The 284-SNP panelachieved: species identification accuracy of 99.4% for all 42 target species (vs. 94.4% for conventional COI barcoding formorphologically similar species pairs); individual identification power of PI = 3.2 x 10-18 (exceeding the 10-12 forensicstandard for individual exclusion); geographic assignment accuracy of 84.4 +/- 4.8% correct assignment to country oforigin (vs. 64.4% for microsatellite-based geographic assignment from the same populations). Casework validation on 84simulated seizure samples (species identity and origin confirmed by chain-of-custody reference material) showed 97.4%correct species identification and 82.4% correct country-of-origin assignment. A SNP-based individual matching systemcorrectly linked 84.4% of paired samples from the same individual (ivory tusks, shark fins matched to carcass specimens)in blind validation. These results provide a validated, operationally deployable SNP forensic platform for 42 CITES-listedpriority species exceeding current forensic standards for species ID, individual ID, and geographic provenance.